2013
DOI: 10.1161/hypertensionaha.112.200972
|View full text |Cite
|
Sign up to set email alerts
|

Intensive Blood Pressure Lowering Increases Cerebral Blood Flow in Older Subjects With Hypertension

Abstract: Abstract-Hypertension is associated with reduced cerebral blood flow (CBF). Intensive (<130/80 mm Hg) blood pressure (BP) lowering in older people might give greater reduction in cardiovascular risk, but there are concerns that this might produce hypoperfusion which may precipitate falls and possibly stroke. We determined the effect of intensive compared with usual BP lowering on CBF in hypertensive older subjects. Individuals aged >70 years with a history of systolic hypertension on 1 or no BP lowering drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 38 publications
3
65
1
Order By: Relevance
“…Furthermore, higher BP among persons with atherosclerosis was associated with a decline in CBF during 5-year follow-up, 31 and previous findings in hypertensive older persons aged ≥70 years showed that CBF increased in persons who were more intensively treated for hypertension. 32 An explanation for our results may be that in our population, consisting of older persons with mild cognitive deficits, BP stays within the range of cerebral autoregulation, whereby CBF remains constant. Because no relation with CBF was found with indicators of autonomic dysfunction, namely BP changes on standing or with BP in subgroups of persons with small vessel disease-related pathologies (prone to have disrupted cerebral autoregulation), we can only speculate that this BP range of maintained cerebral autoregulation seems relatively wide, so that CBF remains stable.…”
Section: Discussionmentioning
confidence: 78%
“…Furthermore, higher BP among persons with atherosclerosis was associated with a decline in CBF during 5-year follow-up, 31 and previous findings in hypertensive older persons aged ≥70 years showed that CBF increased in persons who were more intensively treated for hypertension. 32 An explanation for our results may be that in our population, consisting of older persons with mild cognitive deficits, BP stays within the range of cerebral autoregulation, whereby CBF remains constant. Because no relation with CBF was found with indicators of autonomic dysfunction, namely BP changes on standing or with BP in subgroups of persons with small vessel disease-related pathologies (prone to have disrupted cerebral autoregulation), we can only speculate that this BP range of maintained cerebral autoregulation seems relatively wide, so that CBF remains stable.…”
Section: Discussionmentioning
confidence: 78%
“…Hypothetically antihypertensive drugs may lead to hypoperfusion, aggravating WMHs, but recent study findings make that possibility unlikely. 39,40 Although our study was conducted in an elderly population with hypertension in the Netherlands, approximately 70% in this age range have hypertension, 41 suggesting that our findings may apply to a large part of the general population. Findings of similar studies were in small or selected populations, 7,10,11,15 and may be less readily translatable to the general elderly community.…”
Section: Discussionmentioning
confidence: 88%
“…This line of reasoning may seem counterintuitive, since antihypertensives are thought to decrease cerebral perfusion by reducing blood pressure. It is supported, however, by a small body of evidence showing that the long-term control of high blood pressure may improve systemic and cerebral hemodynamics 7, 8, 10 . We have previously shown that the use of the calcium channel blocker Nicardipine in elderly hypertensive people with a history of coronary artery disease can reduce postprandial hypotension 25 .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, other studies have suggested that chronic blood pressure lowering with regimens that include angiotensin system-blocking medications may preserve cerebral hemodynamics 6 , increase cerebral perfusion 7-10 , and reduce the progression of cerebral white matter hyperintensities 11 , which are associated with abnormal gait and falls. 12, 13 Consistent with these reports, a recent prospective cohort study by Wong et al 14 showed a lower risk of falls among elderly community-dwelling participants taking angiotensin converting enzyme inhibitors (ACEIs) and/or angiotensin receptor blockers (ARBs).…”
Section: Introductionmentioning
confidence: 95%